Analisis Strategi Pemasaran Menggunakan K-Means dan Algoritma Apriori (Studi Kasus: Edulink.id) - Irsandi, Dede; Sokibi, Petrus; Septian, Willy Eka (Jurnal Teknologi Informasi Indonesia (JTII), 2025)
Technological developments in the field of education are increasingly rapid with the presence of various Education Technology (EdTech) platforms. Edulink.id is one of the EdTech startups in Cirebon that focuses on providing School Management Information System (SIMS) and Learning Management System (LMS) services. Edulink.id continues to strive to increase its market penetration. The main challenges faced include a lack of understanding from schools about the many benefits of applications to support productivity and flexibility in learning at school, etc. Research is needed that can formulate a more effective marketing strategy. In this study, the K-Means Algorithm is used to group data based on its characteristics into two groups: prospective and non-prospective customers. And the Apriori Algorithm to determine the pattern of each characteristic of prospective customers to determine a suitable marketing strategy. Through this research, it is hoped that the right marketing strategy can be found to increase awareness and appeal of Edulink.id among educational institutions. Thus, the company can expand its market reach and increase the number of collaborations with potential customers.